Assessment of obtaining sunflower oil from enzymatic aqueous extraction using protease enzymes - D.S. de Aquino; C. Roders; A.M. Vessoni; N. Stevanato; C. da Silva (Grasas y Aceites, 2022)
The aim of this work was to maximize the enzymatic aqueous extraction (EAE) of sunflower seed oil using protease enzymes from the evaluation of various temperatures, pH and enzyme concentrations, using a Box-Behnken experimental design. The effect of a thermal pre-treatment of sunflower seeds on free oil yield (FOY) and oil quality was also determined. In the experimental range adopted, a lower temperature (40 °C) provided higher FOY values, as well as the intermediate pH (8.00) and maximum enzyme concentration (9% v/v). Thermal pre-treatment provided an increase in FOY in the initial extraction times (60 to 180 min) and decreased of the extraction time of 4 to 3 h to obtain the highest FOY value (~16%). The fatty acid composition of the oils obtained showed a predominance of oleic (~47.5%) and linoleic acids (~39.5%). The total phytosterol content in the samples was hardly affected by the heat pre-treatment of the seeds, while the fatty acid profile, tocopherol content and oxidative stability were not altered.